2013
DOI: 10.1080/10810730.2013.768727
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Web-Delivered Tailored Health Behavior Change Interventions

Abstract: Web-based tailored intervention programs show considerable promise in effecting health-promoting behaviors and improving health outcomes across a variety of medical conditions and patient populations. This meta-analysis compares the effects of tailored versus nontailored web-based interventions on health behaviors and explores the influence of key moderators on treatment outcomes. Forty experimental and quasi-experimental studies (N =20,180) met criteria for inclusion and were analyzed using meta-analytic proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
491
5
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 588 publications
(513 citation statements)
references
References 90 publications
14
491
5
3
Order By: Relevance
“…Tailoring can have a positive impact on intervention outcomes and engagement, but this varies between studies and contexts. 31,52 Self-determination theory, 53 a prominent theory of motivation, argues that autonomy is a fundamental human need that facilitates learning. Hence, fostering autonomy by giving users personal choices throughout an intervention should be motivating.…”
Section: Promoting Effective Engagementmentioning
confidence: 99%
“…Tailoring can have a positive impact on intervention outcomes and engagement, but this varies between studies and contexts. 31,52 Self-determination theory, 53 a prominent theory of motivation, argues that autonomy is a fundamental human need that facilitates learning. Hence, fostering autonomy by giving users personal choices throughout an intervention should be motivating.…”
Section: Promoting Effective Engagementmentioning
confidence: 99%
“…Message tailoring has been found to be an effective strategy for improving adherence with a variety of preventive health behaviors in many diverse populations, but has only recently been applied to vaccination. [54][55][56] Using an RCT design, our group (Dempsey et al 57 ) is examining several interventions that provide tailored material to parents about adolescent vaccines via web-based platforms such as iPads or home computers.…”
Section: Parent/patient-level Interventionsmentioning
confidence: 99%
“…Their results showed that computer tailoring is a product of a complex process and its characteristics and effects are influenced by a number of moderating variables, including: (a) location of delivery (b) health behaviour, (c) type of participant population, (d) type of material, (e) number of intervention contacts, (f) length of follow-up, and (g) demographic factors, behaviours, and theoretical concepts used for tailoring (Lustria et al, 2009;Shahab and McEven, 2009;Brouwer et al, 2011;McDonell et al, 2011;Schulz et al, 2012;Lustria et al, 2013). Several computer tailored programmes for smoking cessation developed in countries from North America and Western Europe show promising results, but more research is needed in order to better understand which concepts are essential to stimulate behavioural change for a particular behaviour and for particular segments of the population (Lustria et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, many efforts were done to develop more and more tailored messages and health education programs through the use of information technology, since several studies showed that tailoring messages for each individual can be more effective than presenting generic information in terms of motivating individuals, building their self-efficacy and improving health behaviours (Lustria et al, 2009;Brouwer et al, 2011;McDonell et al, 2011;Schulz et al, 2012;Lustria et al, 2013). Rimer and Kreuter define tailoring as a process for creating individualized communications by gathering and assessing personal data related to a given health outcome in order to determine the most appropriate information or strategies to meet that person's unique needs.…”
Section: Introductionmentioning
confidence: 99%